SOSIALISASI MANFAAT EKOSISTEM MANGROVE SEBAGAI UPAYA PENCEGAHAN ILLEGAL LOGGING DI DESA LATAWE KABUPATEN MUNA BARAT - Rahman; Krisye; Fahrul Rozy Fakaubun (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Utilization of the mangrove ecosystem in West Muna Regency is widely used as firewood, building materials, and other infrastructure development. This utilization has an impact on reducing the area and density of the mangrove ecosystem, thereby reducing the functions and benefits of the mangrove ecosystem. Community participation is very necessary in the sustainable management of mangrove ecosystems. This can happen if the government and the community understand well about the functions and benefits of the mangrove ecosystem for people's lives. This community service activity is a form of independent service as an effort to apply knowledge to advance people's lives through sustainable mangrove ecosystem management. The socialization was carried out using a discussion method with the village government and key figures who played a role in policy making in Latawe Village, West Muna Regency. This service activity provides a deep understanding to the community regarding the introduction of mangrove species, the benefits and importance of conserving the mangrove ecosystem. This is indicated by the follow-up from the village government and community leaders to rehabilitate mangroves on critical lands by involving the full participation of the community. The acquisition of seeds for rehabilitation is carried out independently by the community with funding assistance from the Ministry of Marine Affairs and Fisheries through the Directorate General of Marine Spatial Management and Small Islands. Service activities will continue by continuing to provide direct and indirect assistance in rehabilitation activities starting from determining the location, selecting seeds, sowing seeds, and rehabilitation techniques